Review: is interplay between nanomaterial and membrane technology the way forward for desalination? - Goh, P. S. (John Wiley and Sons Ltd, 2015)
Nanomaterials, which have been the greatest impetus to technological and industrial development in the twenty-first century, have spurred significant innovations and knowledge enhancement in the environmental applications particularly to revolutionize century-old conventional water treatment processes. The established protocols to prepare such hybrid nanocomposites have triggered blossoming interest and to realize most of these applications practically. Similarly, engineered nanomaterials unfold avenues and offer myriad opportunities to explore their impact in various fields and have certainly a great impact on the future of desalination practice. After the review and examination of published materials describing the development of nano-enabled membranes that have been undertaken in recent years, this short review aims at stimulating new ideas and thoughts in the membrane desalination field where we are strongly convinced that it will represent one of the key areas for the realization of a sustainable generation of materials that can benefit mankind. More particularly, this review draws attention to the incorporation of inorganic nanomaterials into conventional polymeric membranes and deals with the practical challenges to implementation of technology for desalination applications.